(untitled) (Journal of the College of Languages (JCL), 2024)
The aims of this study seeks to examine the underlying linguistics features and ideological concept found in the political speech of American EX President, with a specific emphasis on tweets related to Islamophobia and immigration. The study employs a descriptive and interpretive research design. The corpus of the study consisted of 50 purposely selected Tweets, spanning from 2nd January 2015 to 20th May 2020. Data analysis were conducted using Fairclough’s ten-question model (1993). It is found that Trump strategically employed his presidential authority to target Islam and immigration, portraying them as the root cause of terrorism and economic challenges. Trump employed favourable terms while referring to Americans and his supporters, while associating Islam and immigrants with unfavourable descriptors. The findings of this study revealed that Trump employed hyperbole to magnify the perceived threat posed by Islam and immigrants. Trump predominantly employed modal verbs expressing certainty rather than those indicating likelihood in order to demonstrate authority. The future and simple present tenses were commonly used to depict the current threat posed by immigration and the terrorism perpetrated by Islamic groups. The comparative and superlative forms were employed to compare the current state of brightness in the US with its past. The pronouns "we, our, us" were used most frequently to convey a sense of oneness and reduce the perceived barrier between Trump and the audience. Declarative sentences were the most expressive and meaningful acts.